Manajemen Humas dalam Meningkatkan Peran Komite Sekolah di PAUD Sabila Ponorogo - Wilis Werdiningsih (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2020)
School and community are two inseparable things. The community needs schools to educate their children, while schools need the community to support their vision and mission. Therefore the management of school relations with the community (public relations) is an effort of the school to increase good cooperation between schools and the community. This study aims to analyze the implementation of public relations management in schools in increasing the role of school committees. This research uses a qualitative approach, with a type of case study. The results showed that public relations management carried out by schools properly,could increase the role of school committees. The optimal role of the school committee can be to increase effective communication between the school and the guardians of students and can support the implementation of school programs so that educational goals will be easier to achieve.